Optimal. Leaf size=29 \[ \log \left (\frac {1}{\left (3-e^x-x+x^2\right ) \left (x-\log \left (1+e^x\right )\right )}\right ) \]
________________________________________________________________________________________
Rubi [F] time = 1.24, antiderivative size = 0, normalized size of antiderivative = 0.00, number of steps used = 0, number of rules used = 0, integrand size = 0, \(\frac {\text {number of rules}}{\text {integrand size}}\) = 0.000, Rules used = {} \begin {gather*} \int \frac {-3+2 x+e^{2 x} x-3 x^2+e^x \left (1+2 x-2 x^2\right )+\left (-1-e^{2 x}+2 x+e^x (-2+2 x)\right ) \log \left (1+e^x\right )}{3 x-e^{2 x} x-x^2+x^3+e^x \left (2 x-x^2+x^3\right )+\left (-3+e^{2 x}+x-x^2+e^x \left (-2+x-x^2\right )\right ) \log \left (1+e^x\right )} \, dx \end {gather*}
Verification is not applicable to the result.
[In]
[Out]
Rubi steps
\begin {gather*} \begin {aligned} \text {integral} &=\int \frac {-3+2 x+e^{2 x} x-3 x^2-e^x \left (-1-2 x+2 x^2\right )-\left (1+e^x\right ) \left (1+e^x-2 x\right ) \log \left (1+e^x\right )}{\left (3-e^{2 x}-x+x^2-e^x \left (-2+x-x^2\right )\right ) \left (x-\log \left (1+e^x\right )\right )} \, dx\\ &=\int \left (-1+\frac {4-3 x+x^2}{3-e^x-x+x^2}-\frac {1}{\left (1+e^x\right ) \left (x-\log \left (1+e^x\right )\right )}\right ) \, dx\\ &=-x+\int \frac {4-3 x+x^2}{3-e^x-x+x^2} \, dx-\int \frac {1}{\left (1+e^x\right ) \left (x-\log \left (1+e^x\right )\right )} \, dx\\ &=-x-\log \left (x-\log \left (1+e^x\right )\right )+\int \left (-\frac {4}{-3+e^x+x-x^2}-\frac {3 x}{3-e^x-x+x^2}+\frac {x^2}{3-e^x-x+x^2}\right ) \, dx\\ &=-x-\log \left (x-\log \left (1+e^x\right )\right )-3 \int \frac {x}{3-e^x-x+x^2} \, dx-4 \int \frac {1}{-3+e^x+x-x^2} \, dx+\int \frac {x^2}{3-e^x-x+x^2} \, dx\\ \end {aligned} \end {gather*}
________________________________________________________________________________________
Mathematica [A] time = 0.08, size = 30, normalized size = 1.03 \begin {gather*} -\log \left (3-e^x-x+x^2\right )-\log \left (x-\log \left (1+e^x\right )\right ) \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
________________________________________________________________________________________
fricas [A] time = 0.59, size = 26, normalized size = 0.90 \begin {gather*} -\log \left (-x^{2} + x + e^{x} - 3\right ) - \log \left (-x + \log \left (e^{x} + 1\right )\right ) \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
giac [A] time = 0.25, size = 26, normalized size = 0.90 \begin {gather*} -\log \left (-x^{2} + x + e^{x} - 3\right ) - \log \left (-x + \log \left (e^{x} + 1\right )\right ) \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maple [A] time = 0.11, size = 27, normalized size = 0.93
method | result | size |
risch | \(-\ln \left (-x^{2}+x +{\mathrm e}^{x}-3\right )-\ln \left (\ln \left ({\mathrm e}^{x}+1\right )-x \right )\) | \(27\) |
norman | \(-\ln \left (x -\ln \left ({\mathrm e}^{x}+1\right )\right )-\ln \left (x^{2}-{\mathrm e}^{x}-x +3\right )\) | \(29\) |
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maxima [A] time = 0.47, size = 26, normalized size = 0.90 \begin {gather*} -\log \left (-x^{2} + x + e^{x} - 3\right ) - \log \left (-x + \log \left (e^{x} + 1\right )\right ) \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
mupad [B] time = 0.47, size = 26, normalized size = 0.90 \begin {gather*} -\ln \left (\ln \left ({\mathrm {e}}^x+1\right )-x\right )-\ln \left (x+{\mathrm {e}}^x-x^2-3\right ) \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
sympy [A] time = 0.26, size = 22, normalized size = 0.76 \begin {gather*} - \log {\left (- x + \log {\left (e^{x} + 1 \right )} \right )} - \log {\left (- x^{2} + x + e^{x} - 3 \right )} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________